2018
DOI: 10.3390/molecules23123164
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structures of Lignans and Neolignans Isolated from Lauraceae

Abstract: Lauraceae is a good source of lignans and neolignans, which are the most chemotaxonomic characteristics of many species of the family. This review describes 270 naturally occurring lignans and neolignans isolated from Lauraceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 86 publications
(162 reference statements)
0
20
0
Order By: Relevance
“…Lignans are a type of secondary plant metabolite exhibiting diverse structures [ 9 ]. Plants derive a complex array of secondary metabolites from only a handful of relatively simple propenyl phenols [ 10 ]. Biosynthesis of lignans is characterized by a remarkable increase in molecular complexity [ 10 ].…”
Section: Biosynthesis Classification and Presence Of Lignans In Fmentioning
confidence: 99%
“…Lignans are a type of secondary plant metabolite exhibiting diverse structures [ 9 ]. Plants derive a complex array of secondary metabolites from only a handful of relatively simple propenyl phenols [ 10 ]. Biosynthesis of lignans is characterized by a remarkable increase in molecular complexity [ 10 ].…”
Section: Biosynthesis Classification and Presence Of Lignans In Fmentioning
confidence: 99%
“…As exclusion criteria, the following were used: (1) articles in languages apart from English, Portuguese, and Spanish, (2) review articles, (3) full text articles not found, (4) articles without one of the key words, (5) articles discussing a mixture of plants, and (6) articles that did not present the composition of the EOs.…”
Section: Search Strategymentioning
confidence: 99%
“…[3] Lignans are present in Ocotea duckei Vattimo-Gil (Lauraceae), popularly known as "Louro-de-cheiro", "Louro-pimenta" or "Louro-canela" and is widely distributed in the Northeast of Brazil, having in its leaves a furofuran lignan, called yangambin, which is the major constituent of the total fraction of lignoids of the species. [4][5][6] Yangambin has pharmacological effects; analgesic activity, [7] apoptosis induction in tumor cells, [8] anti-PAF, [9] anti-inflammatory, [10] vasorelaxant and hypotensive, [11] as well as leishmanicidal. [12,13] The therapeutic potential of medicinal plants is related to natural products, which are sources of several bioactive molecules and when isolated, their biological activities can be investigated through experimental models.…”
Section: Introductionmentioning
confidence: 99%